2020
DOI: 10.3390/su12093869
|View full text |Cite
|
Sign up to set email alerts
|

Examining Spatial Heterogeneity Effects of Landscape and Environment on the Residential Location Choice of the Highly Educated Population in Guangzhou, China

Abstract: The residential location choice of the highly educated population is an important consideration to construct a livable city. While landscape and environment are important factors, few studies have deeply analyzed the spatial heterogeneity effects of landscape and environment on the residential location choices of a highly educated population. Taking Guangzhou as the sample, we built a livability-oriented conceptual framework of landscape and environment, and constructed datasets for highly educated population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Some studies have found that the abandonment rate of residential quarters tends to increase with distance (i.e., houses in central urban districts are more popular, while houses in suburban areas tend to be more abandoned, which is mostly found in some Chinese cities, such as Hangzhou and Guangzhou). Zhang et al and Wang et al demonstrated that people tend to choose to live in the urban district [7,9]. Another study indicated that houses in suburban areas are more popular compared with those in core areas, and this urban pattern is represented by foreign cities, such as Amsterdam and Rotterdam in the Netherlands [5,6] and Dublin in Ireland [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that the abandonment rate of residential quarters tends to increase with distance (i.e., houses in central urban districts are more popular, while houses in suburban areas tend to be more abandoned, which is mostly found in some Chinese cities, such as Hangzhou and Guangzhou). Zhang et al and Wang et al demonstrated that people tend to choose to live in the urban district [7,9]. Another study indicated that houses in suburban areas are more popular compared with those in core areas, and this urban pattern is represented by foreign cities, such as Amsterdam and Rotterdam in the Netherlands [5,6] and Dublin in Ireland [14].…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al used questionnaires and found that Shanghai residents' migration location remains mostly concentrated in the central city before and after the local population's migration [8]. Wang et al showed the spatial pattern of the residential location of Guangzhou's highly educated population from the perspective of the residential location choice, thereby indicating the characteristics of mainly core areas [9]. Li and Mao's study on Guangzhou also showed that households with higher education levels, higher socio-economic status, or working in government departments and public institutions are more likely to settle in core areas [10].…”
Section: Et Al Used a Large Sample Of Hangzhou To Analyze Spatialmentioning
confidence: 99%
“…Therefore, this study selected the Guangzhou metropolitan area as the research area, which is the central area of Guangzhou, east and north of the Guangzhou Ring Expressway, west of the Guangzhou administrative boundary, and south of the Guangzhou-Gaoming Expressway. According to the reality of Guangzhou's urban construction and development, and referring to the research results of Wang et al on the division of Guangzhou's functional areas [28,29], the Guangzhou metropolitan area is divided into the following four categories: old area, core area, urban district, and suburban, as shown in Figure 1. Taking the typical residential quarters newly built in 2010 as the basic research unit, there are 212 units in total, including 24 in old area, 37 in core area, 70 in urban district, and 81 in suburban.…”
Section: Study Areamentioning
confidence: 99%
“…Among them, many scholars have studied the influence of the physical environment and convenience factors on residential location choice. The factors in the physical environment mainly include: the built environment [5][6][7][8], positive landscape and environment [9][10][11][12][13] and negative landscape and environment [14][15][16]. Life convenience factors include public transportation convenience [17,18], school accessibility [19], employment accessibility [20] and workplace accessibility [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of population sample survey in 2015, it is estimated that the floating population in Guangzhou accounts for 42.44% of its population. Guangzhou's physical environment [13], social environment [25,[30][31][32] and life convenience [33] are complex and diverse and are very suitable for case studies.…”
Section: Introductionmentioning
confidence: 99%